2004
DOI: 10.1093/ptj/84.7.608
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetics and Environment in Lifting Force and Isometric Trunk Extensor Endurance

Abstract: Background and Purpose. Our understanding of what different back performance tests are measuring is limited. The purpose of this study was to investigate the relative contributions of genetics and unique and common environmental factors for 3 tests of back muscle performance in a classic twin analysis. Subjects. The subjects were a populationbased sample of 122 monozygotic and 131 dizygotic male twin pairs aged 35 to 69 years (Xϭ49.9, SDϭ7.7). Methods. Variance component analysis was applied to estimate geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…On the other hand, detecting only 30% of genetic dominance with a power of 80% (Ac = 25%, Dc = 20%, Ec = 10%, As = 15%, Ds = 10%, Es = 20%) would require a sample size of approximately 1925 subjects. The low DZ correlations for MCSA, Fecc and Fcon might be due to sampling error, as in other studies DZ correlations are considerably higher (Arden & Spector, 1997;Ropponen et al, 2004).…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, detecting only 30% of genetic dominance with a power of 80% (Ac = 25%, Dc = 20%, Ec = 10%, As = 15%, Ds = 10%, Es = 20%) would require a sample size of approximately 1925 subjects. The low DZ correlations for MCSA, Fecc and Fcon might be due to sampling error, as in other studies DZ correlations are considerably higher (Arden & Spector, 1997;Ropponen et al, 2004).…”
Section: Discussionmentioning
confidence: 50%
“…Of the 38 measurements obtained using SEM models, 21 adopted AE models and 12 adopted the ACE models. Only two measurements indicated a non‐additive genetic effect (D) . The common environmental effect (C) ranged from 0 to 0.53 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…RES training produced no significant correlations for either zygosity. Previous CX baseline strength assessment studies of twins (Thomis et al 1998;Ropponen et al 2004;Maridaki, 2006;Beunen et al 2011) have revealed a wide range of r MZ of 0.29-0.90. These conflicting results have resulted in strength responses to RES training being labelled as highly environmental, or highly genetic (Thibault et al 1986;Thomis et al 1998).…”
Section: Discussionmentioning
confidence: 97%